Hydrophilic antioxidants from Andean tomato landraces assessed by their bioactivities in vitro and in vivo - Di Paola Naranjo, Romina Daniela; Otaiza, Santiago; Saragusti, Alejandra Cristina; Baroni, María Verónica; Carranza, Andrea del Valle; Peralta, Iris Edith; Valle, Estela Marta; Carrari, Fernando; Asis, Ramón (2017)
Potential nutraceutical properties of hydrophilic antioxidants in fruits of tomato landraces collected in Andean valleys were characterised. Antioxidant metabolites were measured by HPLC-DAD-MS/MS in mature fruits and their biological activities were assessed by in vitro and in vivo methods. In vitro antioxidant capacities were established by TEAC and FRAP methods. For in vivo biological activities we used a procedure based on Caenorhabditis elegans subjected to thermal stress. In addition, Saccharomyces cerevisiae was also used as a rapid screening system to evaluate tomato antioxidant capacity. All tomato accessions displayed significant differences regarding metabolic composition, biological activity and antioxidant capacity. Metabolite composition was associated with geographical origin and fruit size. Antioxidant activities showed significant association with phenolic compounds, such as caffeoylquinic acids, ferulic acid-O-hexosides and rutin. Combination of in vitro and in vivo methods applied here allowed evaluation of the variability in nutraceutical properties of tomato landraces, which could be applied to other fruits or food products